‘...TO NOT ONLY TELL, BUT ALSO TO SHOW, TO SHOW PLENTY...’ THE MAGIC LANTERN AS A TEACHING TOOL IN ART HISTORY AROUND 1900 - Frank KESSLER,Sabine LENK (Fonseca, Journal of Communication, 2023)
The emergence of the magic lantern as a tool for art historical teaching in the second half of the nineteenth century occurs within a larger context of pedagogical reform efforts that promoted visual education. This contribution looks at the infrastructural prerequisites for the large-scale dissemination of magic lantern slides at the time, which made possible the introduction of art historical slides as teaching aids.